POTENTIAL OF BEAUVERIA BASSIANA ON THE INTENSITY OF THE BEMESIA TABACI PEST IN HORTICULTURAL PESTS - Betty Kadir Lahati; Helda Sabban (International Journal of Social Science, 2021)
This study aims to analyze the potency of Beauveria bassiana (Bb) and the best concentration on the population of whitefly Bemesia tabaci on horticultural crops. The method used was a Randomized Block Design (RAK) on eggplant and chili plants with 4 treatments, namely control, Bb 100g/10ltr water, 150g/10ltr water and 200g/10ltr water. Each treatment was repeated 5 times. Data analysis used analysis of variance and continued with the BNT test. The results of the potency test of Beauveria bassiana have the best concentration at 200g/10ltr of water. The average whitefly population on eggplant plants was 65.57%, the population decreased to 6.37% and chili with an average population of 39.37% chili, the population decreased to 15.87%. This is also influenced by agricultural systems in eggplant fields which often rely on synthetic pesticides which cause pests to become resistant and also destroy natural enemies. compared to whitefly pest populations in chili fields which often use organic materials that are far from pest resistance and anti-natural enemies. In addition, the leaves of the eggplant plant are larger than the chili leaves which allow them to lay more eggs and also have a number of trichomes as a shelter for whitefly from natural enemies (predators). The conclusion of the study was that Beauveria Bassiana had good potency at a concentration of 200g/10ltrair against the whitefly Bemesia tabaci on horticultural crops, both eggplant and chili plants. It is suggested to analyze the relationship between leaf structure and preference level of whitefly on horticultural crops.